PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA REPORTER, DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI DI PT SWC - Sumbogo, Ignatius Ario; Diposumarto, Ngadino Surip (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This paper is structured in order to determine the effect of competency, training, and motivation on the performance of the infotainment reporters at PT SWC. The research method that is used is a descriptive analysis with collecting data through literature study and observation using the questionnaires. The research is conducted among the 64 reporters of PT Shandika Widya Cinema. The survey results revealed that an effort to increase the performance of the reporter needs to improve their competencies through continuous, technical training, focused on the journalistic technique, conceptual skills, and behavior. The development focusing on the technical journalism, communication skills, and behavior among the reporter will certainly improve their performance, loyalty, and dedication, which at last will increase the performance of the company. Keywords: competency, training, motivation, performance